Connecting Immune Cell Infiltration to the Multitasking Microglia Response and TNF Receptor 2 Induction in the Multiple Sclerosis Brain - Veroni, Caterina; Serafini, Barbara; Rosicarelli, Barbara; Fagnani, Corrado; Aloisi, Francesca; Agresti, Cristina (Frontiers in Cellular Neuroscience, 2020)
Signaling from central nervous system (CNS)-infiltrating lymphocytes and macrophages is critical to activate microglia and cause tissue damage in multiple sclerosis (MS). We combined laser microdissection with high-throughput real time RT-PCR to investigate separately the CNS exogenous and endogenous inflammatory components in postmortem brain tissue of progressive MS cases. A previous analysis of immune infiltrates isolated from the white matter (WM) and the meninges revealed predominant expression of genes involved in antiviral and cytotoxic immunity, including IFNγ and TNF. Here, we assessed the expression of 71 genes linked to IFN and TNF signaling and microglia/macrophage activation in the parenchyma surrounding perivascular cuffs at different stages of WM lesion evolution and in gray matter (GM) lesions underlying meningeal infiltrates. WM and GM from non neurological subjects were used as controls. Transcriptional changes in the WM indicate activation of a classical IFNγ-induced macrophage defense response already in the normal-appearing WM, amplification of detrimental (proinflammatory/pro-oxidant) and protective (anti-inflammatory/anti-oxidant) responses in actively demyelinating WM lesions and persistence of these dual features at the border of chronic active WM lesions. Transcriptional changes in chronic subpial GM lesions indicate skewing toward a proinflammatory microglia phenotype. TNF receptor 2 (TNFR2) mediating TNF neuroprotective functions was one of the genes upregulated in the MS WM. Using immunohistochemistry we show that TNFR2 is highly expressed in activated microglia in the normal-appearing WM, at the border of chronic active WM lesions, and in foamy macrophages in actively demyelinating WM and GM lesions. In lysolecithin-treated mouse cerebellar slices, a model of demyelination and remyelination, TNFR2 RNA and soluble protein increased immediately after toxin-induced demyelination along with transcripts for microglia/macrophage-derived pro- and anti-inflammatory cytokines. TNFR2 and IL10 RNA and soluble TNFR2 protein remained elevated during remyelination. Furthermore, myelin basic protein expression was increased after selective activation of TNFR2 with an agonistic antibody. This study highlights the key role of cytotoxic adaptive immunity in driving detrimental microglia activation and the concomitant healing response. It also shows that TNFR2 is an early marker of microglia activation and promotes myelin synthesis, suggesting that microglial TNFR2 activation can be exploited therapeutically to stimulate CNS repair.